Irreversible oxygen uptake and thermal expansion in the solid electrolyte oxygen-deficient perovskite Ca(Ti0.8Fe0.2)O3−δ - Bryce G. Mullens; Frederick P. Marlton; Caleb J. Bennett; Matilde Saura-Múzquiz; Maria K. Nicholas; Helen E. A. Brand; Brendan J. Kennedy (APL Materials)
The efficient operation of solid oxide fuel cells for renewable energy generation requires solid electrolytes with high ionic conductivity, thermal stability, and chemical durability. Metal oxide perovskites of the form ABO3 are promising candidates, especially when doped with cations that incorporate interstitial oxygen or oxygen vacancies to enhance ionic conductivity. However, doping can lead to complex and poorly understood crystallographic structures. In this study, we investigate the effects of Fe3+ doping on the orthorhombic Pbnm CaTiO3 perovskite, forming Ca(Ti0.8Fe0.2)O3−δ, and demonstrate the complexity of its phase transitions at operational temperatures. Using synchrotron X-ray diffraction and thermogravimetric analysis, we show that this material undergoes significant oxygen uptake at elevated temperatures, leading to an irreversible expansion of the unit cell and changes in polyhedral coordination upon cooling. These structural modifications are attributed to the partial oxidation of Fe3+ to Fe4+, providing insight into the inconsistencies observed in previous studies of oxygen-deficient perovskites. Our findings highlight the critical role of thermal history and oxygen availability in determining the structural stability and long-term performance of perovskite-based solid electrolytes in solid oxide fuel cells.